LABOUR DIVERSITY MANAGEMENT: THE KEY TO INNOVATION AND ECONOMIC GROWTH - Ignatius Septo Pramesworo; Hadenan Towpek (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Workforce diversity management has become a crucial factor in enhancing innovation and driving economic growth in the era of globalisation. The research method in this study uses the literature method. The results show that effective implementation of diversity management practices not only improves organisational performance, but also contributes significantly to wider economic growth. The research underscores the importance of organisational commitment, inclusive policy development, and diversity awareness training in maximising the potential of a diverse workforce. In conclusion, workforce diversity management is an important strategy that organisations need to adopt to improve competitiveness, drive innovation, and ultimately contribute to sustainable economic growth.